THROMBOCYTOPE NIC PURPURA AFTER INFLUENZA A H1N1 VACCINE - Ramon Bezerra dos Santos, Cicero; Willyam Rodrigues Gomes, Douglas; Gomes Vidal Sampaio, Mariana; Ribeiro de Lima, Liene; de Sousa Cunha, Lorena; da Silva, Eugenia; Brandão, Eduardo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Idiopathic thrombocytopenic purpura (ITP) is probably a disease with autoimmune etiology, defined as an isolated thrombocytopenia not associated with any clinical condition. Other causes related to thrombocytopenia are: HIV infection, systemic lupus erythematosus and druginduced thrombocytopenia. In this report we describe a case of ITP developed after vaccination against influenza A H1N1 in a 64-year-old female patient, hypertensive, offset and in use of antihypertensives, with no history of ITP, after review of clinical history and laboratory tests. The patient’s physical examination revealed pallor, ecchymosis in the trunk, limbs and oral mucosa, with bleeding gums. Absence of adenomegaly and palpable splenomegaly, fever or other signs and symptoms of relevance. The blood count and bone marrow examination showed severe thrombocytopenia with platelet count of 7,000/?L and hypercellularity of the megakaryocytic series (other series were normal), respectively. A transfusion of concentrate platelet was performed and after treatment with specific poly immunoglobulin (IVIG) and corticoids, the patient showed clinical improvement and laboratory indexes were normalized. ITP after vaccine against influenza A H1N1 is a rare event whose causal relationship is difficult to prove, and the diagnosis is based on exclusion of other possible etiologies.